The “limits” of mafia-type association’s crime in front of “mafias business trip” (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
Recently, in Northern Italy, came to light many small criminal groups affiliated to the huge criminal organization known as ‘Ndrangheta. This organization certainly represents one of the most important form of Mafia. The essay aims to clarify if it is correct to consider even the single small group as “mafioso”. Such a label has extremely relevant consequences: in particular, it allows to prosecute the group as an “associazione di tipo mafioso” under section 416-bis of the Italian Penal Code.Keywords: Organized crime; ‘ndrangheta; Characteristics of mafia; elements of the crime of “associazione di tipo mafioso”; mafia local cells.